Tetrakis(1H-imidazole-kappa N-3)(2-phenyl-propanedioato-kappa O-2(1),O-3)nickel(II) - Zhang, Kou-Lin; Diao, Guo-Wang; Ng, S.W. (International Union of Crystallography, 2010)
In the title complex, [Ni(C9H6O4)(C3H4N2)(4)], the Ni-II ion is O,O `-chelated by the phenylmalonato ligand and coordinated by four imidazole ligands in a slightly distorted octahedral geometry. In the crystal structure, symmetry-related molecules are linked by N-H center dot center dot center dot O hydrogen bonds, generating a three-dimensional network.